Hebrew literature and the 1948 war : essays on philology and responsibility - Hever, Hannan (Philological encounters monographs, 2019)
Hebrew Literature and the 1948 War: Essays on Philology and Responsibility is the first book-length study that examines the conspicuous absence of the Palestinian Nakba in modern Hebrew literature.